2021
DOI: 10.3390/nu13051498
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Support in Patients with Severe Acute Pancreatitis-Current Standards

Abstract: Severe acute pancreatitis (SAP) leads to numerous inflammatory and nutritional disturbances. All SAP patients are at a high nutritional risk. It has been proven that proper nutrition significantly reduces mortality rate and the incidence of the infectious complications in SAP patients. According to the literature, early (started within 24–48 h) enteral nutrition (EN) is optimal in most patients. EN protects gut barrier function because it decreases gastrointestinal dysmotility secondary to pancreatic inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 86 publications
0
38
0
1
Order By: Relevance
“…For the route of EN delivery, several randomised controlled trials had shown that there was no difference in terms of mortality, infectious complications, length of hospital stay, or energy balance between nasogastric (NG) and nasojejunal (NJ) feeding in patients with severe acute pancreatitis (SAP) requiring tube feeding [ 1 4 ]. Given the technical difficulty for NJ tube insertion, NG feeding has been recommended as the primary choice for SAP patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the route of EN delivery, several randomised controlled trials had shown that there was no difference in terms of mortality, infectious complications, length of hospital stay, or energy balance between nasogastric (NG) and nasojejunal (NJ) feeding in patients with severe acute pancreatitis (SAP) requiring tube feeding [ 1 4 ]. Given the technical difficulty for NJ tube insertion, NG feeding has been recommended as the primary choice for SAP patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute pancreatitis is a critical illness in pancreatitis characterized by sudden onset and critical conditions. Inappropriate treatment aggravates the condition and is accountable for over 25% acute pancreatitis-associated mortality [ 1 , 2 ]. Clinically, surgery is the mainstay, yet strong evidence suggest that surgical treatment is associated with multiple complications, postoperative body pain, and slow postoperative recovery [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Також існує багато досліджень, присвячених часу початку введення харчових сумішей у пацієнтів з тяжким перебігом ГП. Так, згідно сучасних поглядів, зондове харчування слід починати якомога раніше (24-48 годин від моменту госпіталізації) порівняно з парентеральним харчуванням [2]. Ранній початок ентерального харчування (до 48 годин від моменту госпіталізації) у хворих при тяжкому перебігу ГП асоціюється зі зниженням частоти інфекційних ускладнень на 24 % та смертності на 32 % порівняно з хворими, де ентеральне харчування почалось пізніше [3].…”
unclassified